Analisis Dampak Pembelajaran Online Terhadap Wali Murid, Wali Kelas, dan Siswa Kelas II SD Muhammadiyah 17 Surabaya di Tengah Pandemi Covid-19 - Aden Fani Rahmasari; Fajar Setiawan; Meirza Nanda Faradita (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to obtain information related to the impact of online learning during the Covid-19 pandemic on student guardians, homeroom teachers, and grade II students at SD Muhammadiyah 17 Surabaya. This research is a type of survey research using a qualitative approach. Data collection techniques used interviews, with the research instruments in the form of WhatsApp and Google Form. The WhatsApp instrument is used to conduct interviews via chat with the homeroom teacher. Meanwhile, the Google Form link instrument was sent to the guardians of students and students through the help of the homeroom teacher to find out how each of them responded to online learning in the midst of the Covid-19 pandemic. The results showed that in online learning, parents are required to provide assistance to their children whenever there is online learning activity. As for Mrs. Fitri, the homeroom teacher, online learning makes her have to be ready with the assignments given to her students in order to continue to have activities in carrying out online learning activities even from home. Meanwhile, in online learning as it is today, students are required to be active in doing assignments given by their homeroom teacher.